2009
DOI: 10.1242/jeb.030676
|View full text |Cite
|
Sign up to set email alerts
|

Sugar feedingviatrehalose haemolymph concentration affects sex pheromone production in matedHeliothis virescensmoths

Abstract: SUMMARYLong-distance, female-produced sex pheromones are widespread among moths. Larval feeding provides most of the nutrients for development of these insects but is not thought to influence the de novo production of the fatty-acid derived compounds used as pheromones by most species. Feeding on plant nectar (sugar) by adult moths is important for increasing female fitness and also for the pollination of many plant species. In this paper, I show that feeding on sucrose solution, as opposed to water, increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 41 publications
4
55
0
Order By: Relevance
“…These findings indicate that the pheromone is produced only during a limited period even by the sexual mealybugs, which may save a cost of continuous production. Most pheromones are biosynthesized de novo in specific organs [65,66] and thus require nutrient resources [67]. Terpenoid pheromones of coccoids are considered to be de novo biosynthesized, because their structures are unique, and no compounds with similar skeletons are found in host plants [68].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the pheromone is produced only during a limited period even by the sexual mealybugs, which may save a cost of continuous production. Most pheromones are biosynthesized de novo in specific organs [65,66] and thus require nutrient resources [67]. Terpenoid pheromones of coccoids are considered to be de novo biosynthesized, because their structures are unique, and no compounds with similar skeletons are found in host plants [68].…”
Section: Discussionmentioning
confidence: 99%
“…Adult Lepidoptera commonly feed on carbohydrate in plant nectar, which typically increases female fecundity (Wäckers et al, 2007). In the polyandrous moth Heliothis virescens Fabricius (Lepdioptera, Noctuidae), this adult-acquired carbohydrate (AAC) is also used for pheromone biosynthesis via uptake to hemolymph (as trehalose), followed by glycolysis and pyruvate oxidation to cytosolic acetyl CoA (Foster and Anderson, 2011;Foster, 2009;Foster and Johnson, 2010). Although this demonstrates that pheromone can be made from carbohydrate, we do not know whether this is the sole nutrient used or the relative importance of adult-versus larval-acquired nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cost of calling is assumed to be low (Cardé & Baker, 1984;Alberts, 1992) there is indirect evidence that signalling using pheromones is costly. The decrease in pheromone production associated with resistance to pesticides (Delisle & Vincent, 2002), the use of trehalose and fatty acids as metabolic reservoirs for pheromone biosynthesis (Foster, 2005), the enhancement of sex pheromone production after feeding on sucrose (Foster, 2009;Foster & Johnson, 2010) and the reduced fecundity and survival associated with calling (Harari et al, 2011) all indicate that calling is metabolically expensive. The long period spent calling by large starved females may thus be due to their having greater metabolic reserves and consequently being more able to sustain long and costly periods of calling.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the time spent calling by females fed on sucrose may be a consequence of increased rates of pheromone production. Foster (2009) andJohnson (2010) have demonstrated that females fed on sucrose produce more sex pheromone. Regardless of their body weight, moths are expected to utilize sucrose in several ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation